Comparison of Psychotherapeutic Supervision Paradigms: A Literature Review - Kaluževičiūtė-Moreton, Greta; Skruibis, Paulius; Vaštakė, Marija; Grigutytė, Neringa (Psichologija, 2023)
While there is a considerable body of literature on various psychotherapeutic paradigms and their respective models of supervision, there are not many articles reviewing and comparing different supervisory traditions and supervisor–supervisee relationships. However, this comparison is important on both theoretical and practical levels: it is essential to identify features of supervision that are unique to each paradigm and to determine whether there are any universal or common supervision processes prevalent across a variety of paradigms. This literature review aims to provide a clearer understanding of both commonalities and distinctions among various theoretical paradigms (such as psychoanalytic/psychodynamic, cognitive, and existential/humanistic therapies) and their corresponding models of supervision. To accomplish this goal, the paper examines essential aspects of supervisory relationships within each paradigm, focusing on: a) the key features of the supervision process, b) the supervisor’s role and engagement in the supervision, and c) the primary interventions and factors contributing to the effectiveness of supervision. We identify features that are unique and specific to supervisory relationships in each of the paradigms, as well as features that are common to all three traditions. Considering the theoretical underpinnings of each tradition, the paper discusses epistemological assumptions that could determine the effectiveness of supervision in the context of each therapeutic paradigm.